Strategi Manajemen Rumah Sakit dalam Meningkatkan Responsivitas Pelayanan Gawat Darurat untuk Korban Kecelakaan Lalu Lintas - Ady Purwoto; Slamet Isworo; Enny Rachmani (Universitas Pahlawan Tuanku Tambusai, 2025)
Effective Emergency Room services depend on several factors, including response time, availability of adequate medical facilities, and coordination between hospital units. This study aims to analyze hospital management strategies in improving the responsiveness of Emergency Room services for traffic accident victims, with the hope that the results of this study can provide useful recommendations for hospital management in handling such emergency situations. This study uses a case study design with a qualitative approach, where researchers will analyze the experience and strategies of hospital management in improving the responsiveness of Emergency Room services for traffic accident victims. The results of the study showed that most patients who came to the Emergency Room were non-emergency (70%), and only 30% really needed emergency treatment. This indicates inefficiency in the utilization of Emergency Room services that need to be optimized to ensure that traffic accident victims receive timely treatment. The conclusion of this study is that in order to improve the responsiveness of Emergency services to traffic accident victims in Jabodetabek, hospitals must face several challenges, including inefficiency, limited medical personnel, limited bed capacity, financing challenges from BPJS, in the management of the Emergency Installation with the large number of non-emergency patients coming to the Emergency Installation.